PROBLEMS IN ONLINE LEARNING: A LECTURER’S PERSPECTIVE - Sakhi Herwiana; Elisa Nurul Laili, (Prosiding Seminar Nasional Sains, Teknologi, Ekonomi, Pendidikan dan Keagamaan (SAINSTEKNOPAK), 2021)
During the pandemic Covid-19, the implementation of teaching and learning are conducted online. Online learning can give positive and negative impacts on the students and also lecturers in Hasyim Asy’ari University. This study has described the problems in conducting online learning from the lecturer’s point of view. The subject of the study is the English department students of Hasyim Asy’ari university Tebuireng Jombang. The problems that are faced by the students such as computer literacy, online access, language instruction, participation, and assessment.